THE SOCIAL CONTEXT IN RUSSIA DURING THE SECOND HALF OF THE 19TH CENTURY AND ITS IMPACT ON LITERATURE - Ziyaeva S. R. (Bright Mind Publishing, 2025)
The second half of the 19th century witnessed some of the most significant events in Russian history, both economically and socially. The political unrest of the late 1950s revitalized Russia's intellectual community and led to the abolition of serfdom, which was followed by the peasant reform in 1861. This reform, of course, brought about new economic changes, such as the emergence of a proletariat class as peasants left their land and moved to cities.